Wonosobo Regulation No. 3 of 2014 on Regarding Regional Organization to Achieve Good Governance - Ahmad Faqih (Jurnal Daulat Hukum, 2018)
The problems examined in this study is how effective and efficient arrangement of the bureaucracy of encouraging good governance, whether Wonosobo Regency Regulation No. 3 of 2014 is able to create efficiency and effectiveness of governance in Wonosobo, What are the obstacles and the solution? The research is a qualitative study using sociological juridical approach. Data collection methods used were observation, interview, and documentation. Then analyzed by qualitative analysis methods in order to produce a complete understanding. From the results of this research study concluded that There are two causes of delays in the implementation of the Regulation No. 3 of 2014 on the WTO technical factorsinvolves the placement of a new position at the WTO and non-technical factorsrelated to "political decision" by the government. The effectiveness of the performance of the bureaucracy as the implications of the implementation of the Regulation No. 3 of 2014 on OPD influenced by fundamental structural changes in regional organizations through the establishment of Regulation No. 3 of 2014 on the WTO which replaced Regulation No. 2 Of 2008 on Regional Government Affairs Wonosobo. The impact was to reduce 268/37% structural office with details of the total original echelon becomes 728 to 460 echelon.Downsizing and demotions office structure certainly affects the quality improvement of bureaucratic performance in delivering public services more effective, efficient in carrying out extensive local autonomy, real and responsible, Thus, thethe concept of streamlining the structure of the program structuring and management of bureaucratic apparatus becomes linear simultaneously.Keywords: Regional Organization; Good Governance.